1990
DOI: 10.1161/01.atv.10.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular transport across arterial and venous endothelium in rats. Studies with Evans blue-albumin and horseradish peroxidase.

Abstract: Atherosclerotic lesions are characterized by llpid Infiltration in regions wtth high rates of endothellal cell turnover. The present investigation was designed to elucidate the route of macromolecular transport across vascular endothelium. The aorta and vena cava of male Sprague-Dawley rats were perfusion-flxed after the intravenous in|ection of Evans-blue albumin (EBA) or horseradish peroxidase (HRP). Fluorescence microscopic examination of en face preparation of the aorta stained with hematoxylln allowed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
2
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 22 publications
1
38
2
1
Order By: Relevance
“…Our experimental studies have provided evidence that EC mitosis (12,44) and death (42) are associated with the leakage of macromolecules such as LDL and albumin on an individual cell basis. Studies performed in a number of laboratories, including our own, have shown that these events of accelerated EC turnover occur primarily in areas with disturbed blood flow, e.g., arterial branch points (15,43,60,72). Electron microscopic studies have identified the widening of the intercellular junctions around ECs that are undergoing mitosis or dying and the leakage of the macromolecular tracer horseradish peroxidase (9,27).…”
Section: Effects Of Local Shear Stress Pattern On Klf2 and Mcp-1 Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…Our experimental studies have provided evidence that EC mitosis (12,44) and death (42) are associated with the leakage of macromolecules such as LDL and albumin on an individual cell basis. Studies performed in a number of laboratories, including our own, have shown that these events of accelerated EC turnover occur primarily in areas with disturbed blood flow, e.g., arterial branch points (15,43,60,72). Electron microscopic studies have identified the widening of the intercellular junctions around ECs that are undergoing mitosis or dying and the leakage of the macromolecular tracer horseradish peroxidase (9,27).…”
Section: Effects Of Local Shear Stress Pattern On Klf2 and Mcp-1 Exprmentioning
confidence: 99%
“…30), and there is evidence that sustained, but not transient, activation of JNK is associated with apoptosis (26). Therefore, cyclic stretch without a clear direction, such as that seen in branch points of the arterial tree, would cause a higher frequency of apoptosis (15) and a greater vulnerability to atherogenesis compared with the straight part of the arterial tree, where the cyclic stretch due to the pulsatile pressure is primarily uniaxial in the circumferential direction.…”
Section: Ec Response To Cyclic Uniaxial Stretch As a Feedback Controlmentioning
confidence: 99%
“…One of the first issues that one must address to develop an understanding of the mass transport in these vessels is whether such transport is driven by diffusion and/or convection. In previous mass transport studies of the aorta, rats were injected with a macromolecular tracer, such as horseradish peroxidase (HRP), and were killed after different circulation times (11,35). In an examination of the animals' aortas en face, HRP was found to traverse the endothelium in rare localized spots, rather than uniformly.…”
mentioning
confidence: 99%
“…Stemerman (52) found that macromolecules cross the aortic endothelium in focal spots, not uniformly. Aortic endothelial cells (ECs) in the M phase of mitosis (37,38), ECs in the process of dying and/or sloughing of neighboring dying cells (36), or those containing stigmata (9) temporarily allow easily detectable macromolecules of different sizes, e.g., Evans blue albumin conjugate, horseradish peroxidase (HRP), and Lucifer yellow-low density lipoprotein, through their junctions (7). In rat aorta, the average HRP leak frequency is ϳ1/(2,000 -6,000) cells (7, 36 -38) and leak duration is ϳ1 h (9).…”
Section: Tracer Entry and Accumulation In The Aortamentioning
confidence: 99%
“…In rat aorta, the average HRP leak frequency is ϳ1/(2,000 -6,000) cells (7, 36 -38) and leak duration is ϳ1 h (9). Chuang et al (9) injected rats with HRP, killed them at various circulation times up to 4 min, examined aortic spots en face, and observed very rapid spot grown, with spot diameters ϳ30 m to Ͼ200 m in 4 min. Tompkins (61) injected 125 I-LDL into four squirrel monkeys, killed them 30 min later, harvested numerous vessels, sectioned the vessels extensively, and placed the sections on photographic film.…”
Section: Tracer Entry and Accumulation In The Aortamentioning
confidence: 99%